In Search of East Asian Self-Enhancement - Heine, S.; Hamamura, Takeshi (Sage Publications Inc., 2007)
meta-analysis of published cross-cultural studies of self-enhancement reveals pervasive and pronounced differences between East Asians and Westerners. Across 91 comparisons, the average cross-cultural effect was d = .84. The effect emerged in all 30 methods, except for comparisons of implicit self-esteem. Within cultures, Westerners showed a clear self-serving bias (d = .87), whereas East Asians did not (d = –.01), with Asian Americans falling in between (d = .52). East Asians did self-enhance in the methods that involved comparing themselves to average but were self-critical in other methods. It was hypothesized that this inconsistency could be explained in that these methods are compromised by the “everyone is better than their group’s average effect” (EBTA). Supporting this rationale, studies that were implicated by the EBTA reported significantly larger self-enhancement effect for all cultures compared to other studies. Overall, the evidence converges to show that East Asians do not self-enhance.